10.1016/s1553-3212(07)70179-6 (CrossRef Listing of Deleted DOIs, 2000)
Objective To systematically evaluate the correlations between atherogenic index of plasma (AIP) and the morbidity and mortality of cardiovascular disease (CVD) and investigate the potential dose-response relationship. Methods We comprehensively searched the PubMed, Embase, and Web of Science Core Collection, CNKI, WanFang, and VIP for relevant literature until January 31, 2026. The included studies were cohort studies. The pooled relative risk (RR) and 95% confidence interval (CI) for dose-response relationships were calculated. The linear/nonlinear relationships were evaluated by using restricted cubic splines. Results A total of 24 studies were included for the analysis. The pooled RRs for CVD morbidity and mortality in the highest versus lowest AIP group were 1.35 (95% CI: 1.25 to 1.45) and 1.49 (95% CI: 1.19 to 1.87), respectively. For per 1-unit increase in AIP, the risk of CVD morbidity and mortality increased by 47% (RR = 1.47, 95% CI: 1.32 to 1.64) and 42% (RR = 1.42, 95% CI: 1.18 to 1.71), respectively. Dose-response results showed linear associations between AIP and CVD morbidity (p non-linearity = 0.659), as well as between AIP and CVD mortality (p non-linearity = 0.619). Conclusion This dose-response meta-analysis revealed a correlation between elevated AIP and the morbidity and mortality of CVD. The association has a dose-response profile between AIP and CVD morbidity, suggesting that AIP may serve as a potential predictor of CVD and provide an important basis for early clinical identification and intervention in populations at high risk of CVD.